Suicidality amongst young adults in South-south Nigeria - Oguche, Obielumanii I.; Mariere, Ulunma I.; Adesina, Adedotun D.; Afakwu-Adimoha, Hilda C.; Akakabota, Rukevwe; Abanda, Sotonye C.; Kennis-Briseimo, Ada C. (International Journal Of Community Medicine And Public Health, 2021)
Background: Suicidality is a broad term that encompasses suicidal ideation, suicide plans and suicide attempts. Suicide cuts across all age groups however the young adulthood phase is a critical time for the onset of suicidal behaviours. Often suicide is underreported because of the shame, as such it is a neglected public health problem in our environment. This study seeks to describe the pattern of suicidality and reported health seeking behaviour amongst young people in Bayelsa State. Methods: A descriptive cross-sectional study conducted in the national youth service corps orientation camp, Bayelsa amongst 387 corps members. With the aid of an electronic, self-administered questionnaire adapted from the WHO STEPwise manual on non-communicable diseases; information on socio demographic features, suicide ideation, plan and attempt were obtained. Data was analysed using IBM SPSS version 25.0. Results: The mean age was 25.37 (SD±2.38) years. Most participants were males (58.9%) and single (95.3%). Prevalence of suicidal ideation, plans and attempts was 7.5%, 4.4% and 3.1% respectively. Above one third (35.4%) of those who made suicidal plans in the past 12 months, actually attempted suicide, 4.4% and 2.6% of the respondents had a positive family history of suicide attempt and suicide death respectively. Conclusions: Young adults are a critical population for suicidality. Public health awareness on mental health promotion and uptake of mental health service should be encouraged. Decriminalisation of attempted suicide in Nigeria and better surveillance will enable more effective suicide prevention strategies.